2021
DOI: 10.12957/reuerj.2021.49970
|View full text |Cite
|
Sign up to set email alerts
|

Consulta de enfermagem pré-procedimento de cateterismo cardíaco: avaliação da satisfação do paciente

Abstract: Objetivo: avaliar a satisfação dos pacientes em relação à consulta de enfermagem prévia ao procedimento de cateterismo cardíaco. Método: estudo quantitativo, descritivo, realizado na hemodinâmica de um hospital universitário no estado do Rio de Janeiro, com a participação de 38 pacientes que responderam ao questionário da pesquisa, aprovado pelo Comitê de Ética em Pesquisa. Resultados: predominou o sexo masculino, 20 (53%), com faixa etária acima dos 60 anos, 23 (60%). A hipertensão arterial foi a comorbidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
3
0
8
Order By: Relevance
“…Furthermore, a previous study evaluated the patient's psychological preparation for cardiac catheterization through nursing consultations in the preoperative period in a university hospital in Rio de Janeiro and showed that this intervention promoted trust between patients and nurses, clarified doubts, minimized insecurity and anxiety, improved adherence to established therapeutic actions and helped prevent adverse events (Nascimento et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study evaluated the patient's psychological preparation for cardiac catheterization through nursing consultations in the preoperative period in a university hospital in Rio de Janeiro and showed that this intervention promoted trust between patients and nurses, clarified doubts, minimized insecurity and anxiety, improved adherence to established therapeutic actions and helped prevent adverse events (Nascimento et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing consultation is a tool for the identification of risks and potentialities. It should be guided by clinical reasoning and makes it possible to draw up a strategic plan of nursing diagnoses and interventions to achieve pre-established outcomes (Nascimento et al, 2021).…”
Section: Development and Its Applications In Scientific Knowledgementioning
confidence: 99%
“…For the prevention of various risks, as well as the prevention of risks of adverse events of vascular involvement, nursing care planning should be based on the prior evaluation of important patient information (Kohlman-Trigoboff et al, 2020). Therefore, nursing consultation is fundamental for the elaboration of clinical reasoning, identification and prevention of risks, and determining nursing care in the care of the target patient, pleading the implementation of NCS (Nascimento et al, 2021).…”
Section: Nursing Carementioning
confidence: 99%
“…A realização da angiografia permite a localização (precisa) das obstruções coronarianas, a avaliação da sua extensão e gravidade complementam a estratificação do seu prognóstico e identifica a forma mais apropriada para o tratamento. Neste contexto, os autores abordam sobre a Angioplastia ou Intervenção Coronária Percutânea (ICP), que é um tratamento não cirúrgico das obstruções das artérias no qual é realizado para melhorar o fluxo sanguíneo para o coração por meio de um balão, podendo também ser usado "stents" farmacológicos ou convencionais e próteses endovascular (Nascimento et al, 2021).…”
Section: Complicações No Cateterismo Cardíaco E a Assistência Do Enfe...unclassified